2014
DOI: 10.1021/jo402565t
|View full text |Cite
|
Sign up to set email alerts
|

Employment of Electrodonating Capacity as an Index of Reactive Modulation by Substituent Effects: Application for Electron-Transfer-Controlled Hydrogen Bonding

Abstract: Evaluation of the substituent effect in reaction series is an issue of interest, as it is fundamental for controlling chemical reactivity in molecules. Within the framework of density functional theory, employment of the chemical potential, μ, and the chemical hardness, η, leads to the calculation of properties of common use, such as the electrodonating (ω(-)) and electroaccepting (ω(+)) powers, in many chemical systems. In order to examine the predictive character of the substituent effect by these indexes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…This approach has proven useful for comparing binding abilities between structurally different anions. [17][18][19][20] The knowledge of the molecular features of the receptors has been focused. For example, Gale and co-workers 21 have reported that the acidity of the NH group of some mono-thioureas directs the anion recognition and mathematical models could predict the transmembrane transport ability.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has proven useful for comparing binding abilities between structurally different anions. [17][18][19][20] The knowledge of the molecular features of the receptors has been focused. For example, Gale and co-workers 21 have reported that the acidity of the NH group of some mono-thioureas directs the anion recognition and mathematical models could predict the transmembrane transport ability.…”
Section: Introductionmentioning
confidence: 99%
“…Our last application of the model is in a supramolecular chemistry problem concerned with electrochemically controlled hydrogen bonding (ECHB), which has potential interest in applications such as chemical sensors, molecular electronics, and molecular machines. , In ECHB electronic transfer is used to modify the strength of H-bonds, for example, by reducing a chemical moiety one can increase the negative charge on the H-accepting atom with the concomitant effect of strengthening the H-bond. It is recognized that in nitrobenzenes the nitro groups are usually weak H-acceptors in solution, due to the low polarity of the N–O bond.…”
Section: Applications and Resultsmentioning
confidence: 99%
“…It is recognized that in nitrobenzenes the nitro groups are usually weak H-acceptors in solution, due to the low polarity of the N–O bond. However, the reduction of nitrobenzene increases the negative charge on the oxygen atoms and strengthens the H-bonding with an H-donating guest. , Recently, Martı́nez-González et al studied the substituent effect on reduced nitrobenzenes (ortho- and para-substituted) interacting with 1,3-diethylurea (13du) as H-donating guest. They determined the binding constants ( K b ) that properly describe the reactivity trends.…”
Section: Applications and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is more sensitive for H-bonding interactions [34]. In electrochemistry especially cyclic voltammetry is used to measure the hydrogen bonding interaction, this is due to the electrostatic properties of hydrogen bonds [35].…”
Section: Introductionmentioning
confidence: 99%